Popcorn derived carbon enhances the cyclic stability of MoS2 as an anode material for sodium-ion batteries. (20th June 2019) - Lin, Min; Deng, Mengdie; Zhou, Chaojin; Shu, Yijin; Yang, Lichun; Ouyang, Liuzhang; Gao, Qingsheng; Zhu, Min
Abstract: As a promising anode material for sodium-ion batteries, MoS2 unfortunately suffers from its poor electrical/ionic conductivity and drastic volume variation during the repeated sodiation/desodiation, which lead to unsatisfied rate capability and cycleability. Herein, we employ popcorn, an environment benign biomass, as carbon source to construct MoS2 /popcorn-derived carbon composites. The composite processes a sandwich-like structure due to the intercalation of carbon, realizing sufficient contact of MoS2 monolayers with carbon as well as expanded interspace of (002) layers in MoS2 . The sandwiched structure facilitates electronic transfer as well as Na + diffusion, and is robust to the volume variation during the sodiation/desodiation. As an anode material for sodium-ion batteries, the optimized composite displays a reversible capacity of 475 mAh g −1 at 0.2 A g −1 in the initial cycle, and maintains 406.9 mAh g −1 after 340 cycles. When coupled with NaV0.9 Fe0.1 PO4 in full sodium-ion batteries, the composite delivers a reversible capacity of 278.4 mAh g −1 in the voltage range of 1.0–3.2 V at 1 A g −1, indicating its practical application for sodium-ion batteries. Graphical abstract: Image 1 Highlights: Environment benign biomass, popcorn is employed construct MoS2 /C composites. The composite processes a sandwich-like structure due to the intercalation of PDC. The robust sandwiched structure facilitates Na + diffusion and electronic transfer. The MoS2 /PDC exhibits prominent performance as an anode for sodium-ion batteries.